Tanshinone Capsules Combined With Prednisone for Facial Seborrheic Dermatitis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Fu, Qiang; Huang, Mengya; Tang, Lei; Zheng, Qi; Huang, Fujun; Zhou, Xun; Wang, Shumei (Frontiers in Medicine, 2022)
Background Facial seborrheic dermatitis (FSD), also called facial seborrheic eczema, is a common disease affecting both male and female patients worldwide. Tanshinone is the main bioactive component extracted from the Traditional Chinese Medicine Salvia miltiorrhiza Bunge, which is widely used in treating skin inflammatory diseases. It is necessary to evaluate the clinical evidence for tanshinone capsule treatment of FSD. This study aimed to evaluate the safety and effectiveness of tanshinone capsules combined with prednisone in the treatment of facial seborrheic dermatitis and to provide evidence for clinical practice. Methods Studies were searched in PubMed, the Cochrane Library, the Chinese Biomedical Literature Database, the China National Knowledge Infrastructure, the Chinese Scientific Journal Database, and WanFang Database before October 2021. We also searched for randomized controlled clinical trials (RCT) of tanshinone capsules combined with prednisone on facial seborrheic dermatitis. The meta-analysis was conducted according to the guidelines of the Cochrane Handbook. Two reviewers regulated the research selection, data extraction, and risk of bias assessment, respectively, and a third reviewer was used for consulting when necessary. Review Manager Software 5.3 was used for meta-analysis. Results A total of 10 RCTs with 916 participants were included. Nine studies reported total effectiveness, five studies reported symptom score, seven studies reported adverse events, and four studies reported recurrence rate. The duration of treatment was 4 to 8 weeks. Combination therapy showed better clinical effects compared to the prednisone (OR: 5.82; 95% CI: 3.53, 9.59; p < 0.00001). Combination therapy could repair skin lesions (MD: −0.40; 95% CI: −0.51, −0.30; p < 0.00001), reduce skin erythema (MD: −0.58, 95% CI: −0.67, −0.49; p < 0.00001), relieve skin itch (MD: −0.70; 95% CI −0.77, −0.63; p < 0.00001), and desquamation score (MD: −0.64; 95% CI: −0.71, −0.56; p < 0.00001). Furthermore, combination therapy could reduce adverse events (OR: 0.46; 95% CI: 0.26, 0.84; p = 0.01) and control recurrence rate (OR: 0.22; 95% CI: 0.13, 0.36; p < 0.00001). Conclusions Compared with prednisone, tanshinone capsules combined with prednisone may be effective in the treatment of facial seborrheic dermatitis. However, due to the high risk and ambiguity of bias in the included trials, the conclusion of this study must be interpreted carefully.